Treated wastewater reuse in micro-irrigation: effect of shear stress on biofilm development kinetics and chemical precipitation. Issue 2 (15th January 2021) - Rizk, Nancy; Ait-Mouheb, Nassim; Molle, Bruno; Roche, Nicolas
ABSTRACT: Treated wastewater in micro-irrigation is a promising approach that could be used to decrease the pressure on good quality water resources. However, the clogging of such systems due to biofilm development and chemical precipitation constitute a constraint with the use of treated wastewater (TWW) and lead to lower irrigation system performance. The objective of this work is to study the development of biofilm and composition of fouling due to TWW under shear stresses of 0.7, 2.2 and 4.4 Pa detected along micro-irrigation systems. For this purpose, a Taylor-Couette reactor (TCR) was specifically calibrated for the cultivation of biofilm. The analysis of fouling composition samples (organic and inorganic) shows that biofilm tends to develop under the highest shear stress value (4.4 Pa). Precipitation of calcium carbonate in the form of calcite was observed in conjunction with biofilm growth using X-ray diffractometry (XRD) and thermogravimetric analysis (TGA). These results can be used to ascertain the origins of chemical and biological clogging of drippers and fouling of pipes related to reclaimed water- irrigation. GRAPHICAL ABSTRACT: UF0001